The three musketeers [videorecording (DVD)] - Sheen, Charlie; Sutherland, Kiefer, 1966-; O'Donnell, Chris; Platt, Oliver; Curry, Tim; DeMornay, Rebecca, 1963-; Dumas, Alexandre, 1802-1870 (Walt Disney Home Video, 1999)
Three loyal swordsmen and an eager recruit battle enormous odds in their attempt to defeat an evil royal advisor and a seductive envoy plotting to overthrow the King of France.